Experimental Study on Mechanical Properties of Gas Storage Sandstone and Its Damage Under Temperature and Pressure - Wang, Xiaoping; Wang, Lehua; Zhao, Baoyun; Wu, Yingjie; Yang, Jiaosheng; Sun, Junchang (Frontiers in Earth Science, 2022)
With the ever-increasing demand for energy, energy mining is developing towards the deep underground. In this paper, a conventional triaxial test and a triaxial test at different temperatures (45 MPa confining pressure) have been carried out for sandstone in Hutubi gas storage combined with the damage theory to derive the damage constitutive relationship of the sandstone under thermal-mechanical coupling, and the mechanical properties and damage evolution of sandstone under different temperature were analyzed. The results show that: (1) In the conventional triaxial test, as the confining pressure increases, the peak strength and elastic modulus of the sandstone are higher, and the specimen is partially sheared and damaged. (2) In the triaxial test under the effect of temperature, the peak strength of the sample decreases with the increase of temperature. Compared with the four stages of the conventional triaxial test, the stress-strain curve adds a ductility stage. The failure mode of the sample is mainly micro-cracks extended ductile destruction. (3) Under the thermal-mechanical coupling of sandstone, the greater the initial damage of the sample with the increase of temperature, the greater the strain, the greater the damage. This research results can provide experimental basis and mechanism understanding for the analysis of mechanical properties of gas storage sandstone and the application of deep underground engineering.